La magie du temps et des saisons dans la dramaturgie de Paul Willems - Jakubczuk, Renata (Studia Romanica Posnaniensia, 2021)
In the current article we are examining the presence, importance and significance of weather and seasons in dramatic works of the Belgian writer, Paul Willems. Our study relies upon the methodology of patternsof transitivity proposed by Jean-Pierre Richard. After explaining the principals of our approach, then presenting the corpus of the studied texts and formulating our basic hypothesis concerning the weather, we are reviewing four weather phenomena: the rain, the wind, the snow, and the sun. The completed analysis confirmed the calming role of the rain, the soothing role of the sun and the warning role of the wind. However, we realized, besides the liberating role of the snow in the introduction, its more complex significance because it “weighs heavily” on the life of the characters.